Agricultural companies and adoption of ICT: the case of the ecological olive oil sector in Spain - Medina Viruel , Miguel Jesús; Bernal Jurado, Enrique; Mozas Moral, Adoración; Fernández Uclés, Domingo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
The organic agri-food market in Spain faces an oversupply situation as a result of having one of the largest outputs of these products in the world, together with practically non-existent internal demand. In view of this, ICT (Information and Communication Technologies), has potential for providing an answer to the sector’s commercial problems, owing to the many benefits and strengths arising from its application for business purposes. Accordingly, the present study addresses one of the main organic agri-food sectors in Spain, olive oil, attempting to ascertain whether the characteristics that have been pointed to in the literature as important for explaining the adoption and efficient use of ICT by businesses are in fact present in firms in this sector. Through a field study of a representative sample of the organic olive oil sector, it has identified important structural and organizational weaknesses that hinder these firms’ adoption and use of ICT in their business activities.